2021
DOI: 10.1093/biolre/ioab096
|View full text |Cite
|
Sign up to set email alerts
|

Improved development of mouse somatic cell nuclear transfer embryos by chlamydocin analogues, class I and IIa histone deacetylase inhibitors†

Abstract: In mammalian cloning by somatic cell nuclear transfer (SCNT), treatment of reconstructed embryos with histone deacetylase (HDAC) inhibitors improves efficiency. So far, most of those used for SCNT are hydroxamic acid derivatives—such as trichostatin A—characterized by their broad inhibitory spectrum. Here, we examined whether mouse SCNT efficiency could be improved using chlamydocin analogues, a family of newly designed agents that specifically inhibit Class I and IIa HDACs. Development of SCNT-derived embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…It is beyond any doubt that, in the near future, a wide panel of the investigations from the fields of experimental and applied embryology should have been targeted at the precisely identifying and comprehensively exploring a broad spectrum of morphological, ultrastructural, biochemical, and molecular determinants responsible for increased incidence of the processes leading to initiation and progression of embryo fragmentation. The thorough characterization of the aforementioned determinants seems to be strongly justified in order to recognize the highly predictable biomarkers related to diminishments in not only molecular quality parameters, but also the extracorporeal and peri-implantation developmental capabilities of the ex vivo produced embryos created by such modern ARTs as in vitro fertilization and intracytoplasmic sperm injection in humans and other mammalian species and somatic cell nuclear transfer (SCNT)-mediated cloning in other mammalian species [114][115][116][117][118][119].…”
Section: Discussionmentioning
confidence: 99%
“…It is beyond any doubt that, in the near future, a wide panel of the investigations from the fields of experimental and applied embryology should have been targeted at the precisely identifying and comprehensively exploring a broad spectrum of morphological, ultrastructural, biochemical, and molecular determinants responsible for increased incidence of the processes leading to initiation and progression of embryo fragmentation. The thorough characterization of the aforementioned determinants seems to be strongly justified in order to recognize the highly predictable biomarkers related to diminishments in not only molecular quality parameters, but also the extracorporeal and peri-implantation developmental capabilities of the ex vivo produced embryos created by such modern ARTs as in vitro fertilization and intracytoplasmic sperm injection in humans and other mammalian species and somatic cell nuclear transfer (SCNT)-mediated cloning in other mammalian species [114][115][116][117][118][119].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Yamanaka [ 29 ] proposed that the Kac level in the donor cell genome appeared to be positively correlated with the development rate of SCNT embryos of miniature pigs. Previous studies showed that Kac modification was enhanced by adding HDACi to the somatic cells to improve the developmental competence of mouse SCNT embryos [ 30 ]. In our study, when MDSCs, FFCs, and EFCs were treated with 10 mM NaCr for 24 h, the Kac levels of the three types of somatic cells were not markedly decreased or increased.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mouse cloning efficiency could be improved by chlamydocin analogues, which are a family of newly designed agents that specifically inhibit Class I and IIa HDACs. The results showed that one of the chlamydocin analogues, Ky-9, strongly promoted the development of cloned mouse embryos to a level similar to that of TSA [141].…”
Section: Ameliorate Global Dna Methylation and Histone Acetylation Us...mentioning
confidence: 95%